Ojibwe sky star map constellation guidebook : an introduction to Ojibwe star - Lee, Annette S.; Wilson, William (Artist); Tibbetts, Jeffrey; Gawboy, Carl ([Native Skywatchers], 2014)
Presents an interdisciplinary guide to Ojibwe sky star map constellations and star knowledge that covers astronomy, culture, art, and language. Features color illustrations and information on stars, constellations, and planets in relation to the four seasons.